Synthesis, Characterization, Theoretical Studies and Bioactivity of Pd(II), Rh(III), Ru(III) and Pt(IV) Complexes with 1,8-Naphthalimide Derivative - Al-Hasani, Rehab Abd Almahdi; Abed, Asia Hameed; Ibrahim, Sura Khaleel (Iraqi Journal of Science, 2022)
A New Mannich base [N-(4-morpholinomethyl)-1,8-naphthalimide] (L), was synthesized and characterized by C.H.N analysis, FTIR, UV-Vis and 1HNMR spectral analysis. Metal ion complexes of (L) with Pt(IV), Rh(III), Ru(III) and Pd(II) ions were prepared and characterized by FT-IR, and UV-Vis spectroscopy, elemental analysis (C.H.N), flame atomic absorption techniques as well as magnetic susceptibility and conductivity measurements. The results showed that metal ion complexes for all complexes were found in [1:2] [M:L] ratio except for Pd(II) complex which was found in [1:1] [M:L] ratio. Hyperchem-8 program has been used to predict structural geometries of the (L) and it's complexes in gas phase. The electrostatic potential (EP) of the (L) was calculated. Furthermore, the heat of formation ( ), binding energy ( ), vibration spectra, electronic spectra and bond length for the ligand (L) and its metal ion complexes were calculated by PM3 methods. The antimicrobial activity of (L) and its complexes has been extensively studied against pathogenic bacteria such as (Pseudonomous aerugionosa) as gram negative and (Bacillus Subtilis) as gram positive and fungi (Candida albicans) and (Aspergillus flavus) by agar-well diffusion technique.